FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PETUGAS DALAM PELAKSANAAN PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA - Novita, Yuliana; Harnani, Yessi; Rienarti Abidin, Aldiga; Renaldi, Reno; Satria Efendi, Ahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Performance in a health agency greatly influences health programs. Performance also really needs to be paid attention to in an organizational or program activity, one of which is the Healthy Indonesia Program with a Family Approach (PISPK) activity, which is one of the programs prioritized in current health development. The aim of the research is the factors that influence the performance of officers in implementing the Healthy Indonesia Program with a Family Approach in the Pekanbaru Community Health Center Work Area. This type of research is quantitative with a cross sectional design. The research population was PISPK officers, a sample of 65 people using a total sampling technique. Data processing was carried out using computerization and analyzed univariately, bivariately and multivariately. The research results showed that 47.7% of respondents had poor performance, 38.5% had never received training, 53.8% had worked for 1-5 years, 46.2% had transactional leadership, 44 had not received awards, 6%, 41.5% had a low workload, 56.9% were dissatisfied with their work and 64.6% had low work motivation. The bivariate results obtained showed a relationship between training (p.value = 0.019), length of service (p.value < 0.017), and workload (p.value = 0.020), unrelated variables namely leadership (p.value = 0.112), rewards (p.value = 0.182), incentives (p.value = 0.687) and motivation (p.value = 0.807), and workload are the dominant factors related to the performance of health workers in implementing the Healthy Indonesia Program with a Family Approach. It is hoped that the Local Health Center will provide incentives according to the specified time and provide bonuses to health workers.Keywords: Performance, Healthy Indonesia Program with a Family Approach